Quantitative phase analysis of bauxites and their dissolution products - Gan, B.; Taylor, Zoe; Xu, B.; Van Riessen, Arie; Hart, Robert; Wang, Xiaodong; Smith, P. (Elsevier, 2013)
Quantitative phase analysis for four bauxite samples sourced from different geological regions was conducted with Rietveld refinement of synchrotron sourced X-ray diffraction (XRD) data. Minor and trace phases were concentrated using (i) caustic leaching to selectively remove phases such as gibbsite, boehmite and kaolinite and (ii) dithionite–citrate–bicarbonate leaching to selectively remove the iron oxide phases such as goethite and hematite, and reanalysed. Bauxites are normally recognised as very difficult samples for quantitative phase analysis (QPA). The use of synchrotron XRD in this paper allowed characterisation with QPA, crystallite size determination and elemental substitution in some phases. Elemental composition analysis by X-ray fluorescence demonstrated close agreement with the diffraction data and allowed an estimate of the composition of the non-crystalline component of the bauxite samples. Other characterisation techniques used include thermogravimetric/differential scanning calorimetry to determine the phase transitions and mass loss, and transmission electron microscopy/energy dispersive spectroscopy to capture the morphology of the crystallites in the bauxite samples.